(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate of the outcomes of postpartum hemorrhage management at Hanoi Obstetrics and Gynecology Hospital in 2023–2024. Material and Methods: A cross-sectional descriptive study was conducted on 237 cases diagnosed with and treated for postpartum hemorrhage following vaginal delivery within 24 hours at Hanoi Obstetrics and Gynecology Hospital from January 2023 to December 2024. Results: The mean age of the study population was 27.55 ± 4.66 years, with the majority aged 19–34 years (90.0%). Most women who delivered vaginally were diagnosed with postpartum hemorrhage after placental delivery (90.7%), with uterine atony being the most common cause (73%). The main management modalities included uterotonic agents (90.3%), uterine exploration (88.2%), and repair of perineal lacerations (64.6%). Ringer’s lactate was the most frequently used intravenous fluid (95.4%), and most patients did not require blood product transfusion. The management success rate was 96.2%, with a mean postpartum follow-up duration of 3 days. Conclusion: Postpartum hemorrhage predominantly occurred in younger women and was most commonly detected after placental delivery, with uterine atony being the leading cause. Management mainly involved medical therapy and simple interventions, resulting in a high success rate, and most patients did not require blood product transfusion. The mean postpartum follow-up duration was approximately 3 day.